Contribution of the Nelson R. Mandela School of Medicine to a socially accountable health workforce - Amy Clithero-Eridon; Danielle Albright; Cameron Crandall; Andrew Ross (AOSIS, 2019)
Background: A socially accountable health professional education curriculum aims to produce fit-for-purpose graduates to work in areas of need. 'Fit-for-purpose' can be assessed by monitoring graduate practice attributes. Aim: The aim of this article was to identify whether graduates of 'fit-for-purpose' programmes are socially accountable. Setting: The setting for this project was all 37 district hospitals in the KwaZulu-Natal province in Durban, South Africa. Methods: We surveyed healthcare professionals working at district hospitals in the KwaZulu-Natal province. We compared four social accountability indicators identified by the Training for Health Network Framework, comparing medical doctors educated at the Nelson R. Mandela School of Medicine (NRMSM) with medical doctors educated at other South African and non-South African medical schools. In addition, we explored medical doctors' characteristics and reasons for leaving or staying at district hospitals. Results: The pursuit of specialisation or skills development were identified as reasons for leaving in the next 5 years. Although one-third of all medical doctors reported an intention to stay, graduates from non-South African schools remained working at a district hospital longer than graduates of NRMSM or other South African schools and they held a majority of leadership positions. Across all schools, graduates who worked at the district hospital longer than 5 years cited remaining close to family and enjoyment of the work and lifestyle as motivating factors. Conclusion: Using a social accountability approach, this research assists in identifying areas of improvement in workforce development. Tracking what medical doctors do and where they work after graduation is important to ensure that medical schools are meeting their social accountability mandate to meet community needs.